PHYTOBIOGEOGRAPHY OF THE SPECIES ASSOCIATED WITH DRY INTERMOUNTAIN VALLEYS IN THE CHAMA RIVER MIDDLE BASIN, MÉRIDA, VENEZUELA - ARANGUREN B., Anairamiz; COSTA, Manuel; GUEVARA, José; CARRERO, Omar (Acta Botánica Venezuelica, 2016)
Dry intermountain valleys in the Andes constitute areas of ecological interest due to their unique climate, flora, and soils. In the state of Mérida (Venezuela), a xerophytic or semiarid enclave located in Ejido-Estanques in the middle basin of the Chama river was studied. The floristic inventory showed 28 families with 62 species (3 endemics) and seven new reports. The phytogeographic analysis indicates that all species belong to two floristickingdoms, except for two cosmopolitan and cultivated species. Nine biogeographical regions and 37 provinces are represented, belonging to the Neotropical-Austroamerican kingdom, the Neotropical subkingdom. The most frequent are the Colombian Andean and Guajirean-Caribbean provinces, although other species have a Caribbean-Mesoamerican and Guayanan-Orinoquian origin. There are several natural ecosystems which suggest a drier climate in the past, with different floristic elements from those in adjacent more humid ecosystems. Fitobiogeografía de especies asociadas a un valle intermontano seco en la cuenca media del río Chama, Mérida, Venezuela Los bolsones xerofíticos de los Andes de Mérida constituyen enclaves de interés ecológicodadas sus condiciones únicas climáticas, edáficas y florísticas. En el estado Mérida (Venezuela) se estudió el bolsón xerofítico o enclave semiárido en Ejido-Estanques, en el valle medio del río Chama. El inventario florístico revela 28 familias, 62 especies, de las cuales tres son endémicas y siete son nuevos registros para la zona. El análisis fitogeográficomuestra dos reinos aunque hay dos especies cosmopolitas y cultivadas. Nueve regiones biogeográficas y 37 provincias están representadas, pertenecienets al reino Neotropical-Austroamericano, subreino Neotropical. Resaltan como frecuentes la provincia Andina Colombianay la Guajireña-Caribeña de la Neogranadina; también se encontraron plantas de origen Caribe-Mesoamericano y de la región Guayana-Orinoquense. Hay varios ecosistemasnaturales que revelan un clima seco en el pasado y elementos florísticos muy disímiles de los ecosistemas aledaños.